Penegakan Hukum Terhadap Pelaku Penyalahgunaan Ganja Sebagai Pengobatan - Priska Dwi Wahyurini (DE LEGA LATA: JURNAL ILMU HUKUM, 2021)
Law enforcement is a process as the application of discretion that involves in making decisions is not strictly regulated by the rule of law but has an element of personal judgment. The problem of narcotics abuse is a complex problem in its solution. The problem in this study is a juridical review of the use of cannabis as a treatment and legal protection of cannabis users as a treatment. This type of research uses normative juridical. The research approach is a legal, conceptual and case approach. In the Narcotics Law to legally use Group I Narcotics is the use for the benefit of the development of science and technology in limited quantities, accompanied by very strict provisions and treatment. There is still no positive law in Indonesia that regulates the permissibly of marijuana to be used as a treatment or palliative therapy. The legalization of cannabis has not yet received approval from the National Narcotics Agency and the government to use marijuana as a treatment. There is a special agency from the Government of Indonesia that facilitates the Indonesian people to use marijuana as a treatment so there is direct control concerning administering marijuana actually used in accordance with a doctor's prescription. Article 41 of the Narcotics Law required a renewal of Narcotics Group I which cannot only be used for the purposes of developing science and technology but can also be used for palliative medicine or therapy with close supervision.